Euglycemic Diabetic Ketoacidosis Associated With Sodium–Glucose Cotransporter Type 2 Inhibitors in Patients With Type 2 Diabetes Mellitus Receiving Oral Therapy. (April 2019) - Dull, Ryan B.; Spangler, Mikayla L.; Knezevich, Emily L.; Lau, Britney M.
Introduction and Objective: Postmarketing reports and warnings of serious adverse events such as diabetic ketoacidosis (DKA) have raised concern regarding the safety of sodium–glucose cotransporter 2 inhibitors (SGLT2i). This report describes 2 cases of symptomatic SGLT2i-associated euglycemic DKA (euDKA) leading to hospitalization in patients with type 2 diabetes mellitus (DM) previously well controlled on oral medications. Case Reports: Subject 1 is a 55-year-old female admitted with euDKA precipitated by infection and managed with intravenous insulin. This case was notable for a delayed diagnosis of euDKA and lack of clinical improvement despite withholding dapagliflozin. Subject 2 is a 62-year-old male admitted with euDKA precipitated by infection. His clinical condition improved rapidly and euDKA responded to withdrawal of empagliflozin alone. Discussion: Applying the Naranjo adverse medication reaction probability scale to each case (subject 1 score = 3 points; subject 2 score = 4 points) suggests these are possible adverse reactions to SGLT2i. Data from randomized controlled trials suggest DKA events in adults with type 2 DM receiving SGLT2i are rare and similar to placebo. However, data from a large cohort suggest these events occur more frequently and are associated with a 2-fold increased risk of DKA. Conclusion: This class of medications may be associated with a higher real-world risk of DKA in adults with type 2 DM than previously reported. Patients prescribed these medications should receive vigilant assessment for features of traditional DKA as well as euDKA.